The Higher Order Thinking Skills (HOTS) in Activities of the Lesson Plan by in Service Teachers of the Teacher Certification Program - Gustiana, Putri Dwi; Yunita, Wisma; Maisarah, Ira (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The aim of this research was to find out the obstacles faced by teachers in implementing Higher Order Thinking Skill in activities of the lesson plan by in-service teachers of the teacher certification program. This mixed method research used a checklist, and interview as the instruments. This research includes 40 lesson plans that consist of 20 lesson plans for action 1 and 20 lesson plans for action 2. The results of this research revealed that Most HOTS were found with the highest frequency in the core activities and close activities, whereas HOTS were found with the lowest frequency in the preliminary activities. It implied that teachers emphasized the well-distribution of HOTS just in the core and close activities. The interview results revealed that teachers’ challenges encompassed constraints related to time, facilities, teacher competence, student abilities, and student motivation. Additionally, some teachers faced challenges in both preliminary and close activities.